Breakfast skipping and cognitive and emotional engagement at school: a cross-sectional population-level study. Issue 12 (16th December 2022) - Moller, Hero; Sincovich, Alanna; Gregory, Tess; Smithers, Lisa
Abstract: Objective: Research on the consequences of breakfast skipping among students tends to focus on academic outcomes, rather than student well-being or engagement at school. This study investigated the association between breakfast skipping and cognitive and emotional aspects of school engagement. Design: Cross-sectional study using data from a population-level survey of children and adolescents' well-being and engagement at school. Linear regression with adjustment for confounders was used to estimate the effect of breakfast skipping on school engagement. Setting: Government schools (i.e. public schools) in South Australia. Participants: The participants were students, Grades 4–12, who completed the Wellbeing and Engagement Collection in 2019. The analysis sample included 61 825 students. Results: Approximately 9·6 % of students reported always skipping breakfast, with 35·4 % sometimes skipping and 55·0 % never skipping. In the adjusted linear regression models, children and adolescents who always skipped breakfast reported lower levels of cognitive engagement ( β = −0·26 (95 % CI −0·29, −0·25)), engagement with teachers ( β = −0·17 (95 % CI −0·18, −0·15)) and school climate ( β = −0·17 (95 % CI −0·19, −0·15)) compared with those who never skipped breakfast, after controlling for age, gender, health, sleep, sadness and worries, parental education, socio-economic status and geographical remoteness. Conclusion: Consistent with our hypothesis, skipping breakfast was associated with lower cognitive and emotional engagement, which could be due to mechanisms such as short-term energy supply and long-term health impacts. Therefore, decreasing the prevalence of breakfast skipping could have a positive impact on school engagement.